Phonological and orthographic cues enhance the processing of inflectional morphology. ERP evidence from L1 and L2 French - Carrasco-Ortiz, Haydee; Frenck-Mestre, Cheryl (Frontiers in Psychology, 2014)
We report the results of two ERP experiments in which Spanish learners of French and native French controls show graded sensitivity to verbal inflectional errors as a function of the presence of orthographic and/or phonological cues when reading silently in French. In both experiments, verbal agreement was manipulated in sentential context such that subject verb agreement was either correct, ill-formed and orally-realized, involving both orthographic and phonological cues, or ill-formed and silent which involved only orthographic cues. The results of both experiments revealed more robust ERP responses to orally-realized than to silent inflectional errors. This was true for L2 learners as well as native controls, although the effect in the learner group was reduced in comparison to the native group. In addition, the combined influence of phonological and orthographic cues led to the largest differences between morphosyntactic conditions. Overall, the results suggest that the presence of phonological cues may enhance L2 readers’ sensitivity to morphology but that such may appear in L2 processing only when sufficient proficiency is attained. Moreover, both orthographic and phonological cues are used when available.